(untitled) (Халықаралық қатынастар және халықаралық құқық сериясы, 2016)
The purpose of the article is to describe the main particularities of the legal regulation of social networks in the Republic of Kazakhstan and to highlight the most often legal problems. The authors underline the significant role of social networks in the formation of the users’ ideology and priorities. The legal regulation of social networks in the Republic of Kazakhstan does not correspond to the sufficient level of seriousness, leading to repeated violations of law by using this type of resource. Thus, the main objective today is to create an adequate legal act, devoted to the regulation of the activities in social networks.